English as a Foreign Language (EFL) Teachers’ Perceptions of Fair Assessment - Seden, Kinley; Svaricek, Roman (Neveléstudomány | Oktatás – Kutatás – Innováció, 2019)
Although assessment is crucial, we know less about how assessment is understood and administered by teachers. The following study explored insight into lower secondary EFL teachers’ perceptions of fair assessment and the types of assessment that worked and those that did not work in their classes. The data was processed through individual semi-structured interviews with ten (grades 7-9) English as a Foreign Language teachers representing seven lower secondary schools in the Czech Republic. The concept of fair assessment and assessment that worked or not were identified, analysed and interpreted. The findings showed use of specific and focused assessment criteria and assessment that is non-judgemental, honest and transparent as fair assessment. Results indicated verbal assessment to be the best example of assessment that work while self-peer as assessment that doesn’t work with students.